Enteric pH responsive cargo release from PDA and PEG coated mesoporous silica nanoparticles: a comparative study in Drosophila melanogaster - Sapre, Nidhi; Chakraborty, Rusha; Purohit, Poorvi; Bhat, Suresh; Das, Gaurav; Bajpe, Sneha R. (RSC Advances, 2020)
Physiological stimulus-specific cargo release from nanoparticle carriers is a holy grail of drug delivery research. While the majority of such work is carried out in vitro with cell lines, widespread use of common mammalian model systems - mice and rats - is difficult due to the associated cost and regulatory restrictions. Here we use the inexpensive, easily reared, excellent genetic model system Drosophila melanogaster to test pH responsive cargo release from widely used mesoporous silica nanoparticles (MSNs) coated with pH sensitive polydopamine (PDA) and polyethylene glycol (PEG) polymers. We synthesized 650 +/- 75 nm diameter PDA or PEG coated mesoporous silica nanoparticles loaded with a fluorescent dye and fed to individual adult flies. Subsequently, the passage of the particles were monitored through the fly gut. As in mammals, the fly intestine has multiple pH specific zones that are easily accessible for imaging and also genetic, biochemical or physiological manipulations. We observed that both the species of MSNs ruptured around the acidic (pH < 4.0) middle midgut of the flies. PEG coated particles showed sharper specificity of release in the acidic middle midgut of flies than the PDA coated ones and had less tendency to clump together. Our results clearly show that the Drosophila gut can be used as a model to test pH responsive biocompatible materials in vivo. Our work paves the way for greater use of Drosophila as an in vivo complete systemic model in drug delivery and smart materials research. It also suggests that such specific delivery of chemical/biological cargo can be exploited to study basic biology of the gut cells and their communication with other organs.